ADAMTSL2 gene variant in patients with features of autosomal dominant connective tissue disorders. Issue 3 (27th December 2020) - Steinle, Jacob; Hossain, Waheeda A.; Lovell, Scott; Veatch, Olivia J.; Butler, Merlin G.
Abstract: Ehlers‐Danlos syndrome (EDS) consists of a heterogeneous group of genetically inherited connective tissue disorders. A family with three affected members over two generations with features of Dermatosparaxic EDS (dEDS) autosomal dominant transmission was reported by Desai et al. and having a heterozygous nonsynonymous missense variant of ADAMTSL2 (c.1261G > A; p. Gly421Ser). Variation in this gene is also reported to cause autosomal recessive geleophysic dysplasia. We report five unrelated patients with the Gly421Ser variant identified from a large series of patients presenting with features of connective tissue disorders, each with a positive family history consistent with autosomal dominant transmission. Clinical features of a connective tissue disorder included generalized joint hypermobility and pain with fragility of internal and external tissues including of skin, dura, and arteries. Overall, our analyses including bioinformatics, protein modeling, and gene‐protein interactions with the cases described would add evidence for the Gly421Ser variant in ADAMTSL2 as causative for variable expressivity of autosomal dominant connective tissue disorders.